A high-energy conversion-type cathode activated by amorpholization for Li rechargeable batteries. Issue 37 (18th May 2022) - Lee, Yongseok; Kang, Jungmin; Ahn, Jinho; Ko, Wonseok; Park, Hyunyoung; Lee, Seokjin; Lee, Sangyeop; Yoo, Jung-Keun; Kim, Jongsoon
Abstract : An amorphorized Cu(PO3 )2 /C composite (A-CPO/C) achieves outstanding electrochemical performances compared to a low-crystalline Cu(PO3 )2 (LC-CPO/C) composite. Abstract : Although conversion-type electrodes deliver larger theoretical capacities than intercalation-type electrodes, their application as practical cathodes for Li rechargeable batteries is hindered by their intrinsically sluggish kinetics and low operating voltage. In this study, we demonstrate that the conversion-type electrochemical behaviors of Cu(PO3 )2 in a Li-cell system are highly enhanced by amorpholization and carbon-mixing. In particular, the presence of the (PO3 ) − polyanion in the structure enables a much higher operation voltage of Cu(PO3 )2 relative to that of other conversion-type metal-oxide electrodes, resulting from the inductive effect by phosphorus with high electronegativity. As a result, the amorphorized Cu(PO3 )2 /C composite delivers not only a large reversible capacity of ∼240 mA h g −1 at 12 mA g −1 but also an average operation voltage of ∼2.8 V ( vs. Li + /Li). Even at a high current density of 1200 mA g −1, up to ∼60% of the specific capacity at 12 mA g −1 is retained. Furthermore, the capacity retention after 300 cycles at 480 mA g −1 is ∼77% of the initial capacity. This outstanding power capability and cyclability of the amorphorized Cu(PO3 )2 /C composite differ markedly from the poor electrochemical properties of the well-crystallized Cu(PO3 )2 /C composites, indicating the enhanced kinetics of the conversion reaction in Cu(PO3 )2 by amorpholization. In addition, the reversible conversion-reaction mechanism of Cu(PO3 )2 in a Li-cell system is demonstrated through various experimental measurements.